2007
DOI: 10.1111/j.1365-2958.2007.05918.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of T‐DNA integration into the chromosomes ofMagnaporthe oryzae

Abstract: SummaryAgrobacterium tumefaciens-mediated transformation (ATMT) has become a prevalent tool for functional genomics of fungi, but our understanding of T-DNA integration into the fungal genome remains limited relative to that in plants. Using a model plantpathogenic fungus, Magnaporthe oryzae, here we report the most comprehensive analysis of T-DNA integration events in fungi and the development of an informatics infrastructure, termed a T-DNA analysis platform (TAP). We identified a total of 1110 T-DNAtagged l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 61 publications
11
62
2
Order By: Relevance
“…The sequences flanking the T-DNA insertion sites were analyzed in the 33 mutants, and results correlated with what has been found in other laboratories (Choi et al, 2007;Meng et al, 2007). The majority of insertions were located in promoter regions (51%) and coding sequences (24%).…”
Section: Phil-ps Surfaces Allow the Identification Of Genes Required supporting
confidence: 49%
See 1 more Smart Citation
“…The sequences flanking the T-DNA insertion sites were analyzed in the 33 mutants, and results correlated with what has been found in other laboratories (Choi et al, 2007;Meng et al, 2007). The majority of insertions were located in promoter regions (51%) and coding sequences (24%).…”
Section: Phil-ps Surfaces Allow the Identification Of Genes Required supporting
confidence: 49%
“…Several intergenic T-DNA insertions were surrounded by EST and MPSS signatures, suggesting that these regions contained functional genes (see Supplemental Figure 4 online). A detailed analysis of flanking sequences in 92 T-DNA random insertions in the M. oryzae genome showed that the most common event (78.3%) during the T-DNA integration in M. oryzae are deletions ranging from 1 to 1950 bp; the most frequent deletions are <35 bp (Choi et al, 2007). Therefore, it is possible that some of the T-DNA mutants have more than one gene affected at the locus of the T-DNA insertion.…”
Section: Phil-ps Surfaces Allow the Identification Of Genes Required mentioning
confidence: 99%
“…Our results mean that a nonexact joining of T-DNA and fungus genomic DNA occurred during the integration event. Information on the pattern of T-DNA integration in fungi was very limited, with only a few T-DNA insertion sites having been characterized in several species transformed using A. tumefaciens (Bundock et al, 1995;Mullins et al, 2001;Leclerque et al, 2004, Choi et al, 2007Li et al, 2007;Meng et al, 2007). The most significant contribution for understanding the mechanisms and characteristics of T-DNA integration has been given from analysis of Magnaporthe oryzae transformants.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant contribution for understanding the mechanisms and characteristics of T-DNA integration has been given from analysis of Magnaporthe oryzae transformants. Choi et al (2007) conducted a broad analysis of T-DNA insertion sites in transformants of M. oryzae and showed that exact joining (without deletion, addition, and microhomology) of T-DNA and genomic DNA occurred in only 14.1% of the integration events. Non-exact joining of T-DNA and fungus genomic DNA occurred very frequently.…”
Section: Resultsmentioning
confidence: 99%
“…polymerase chain reaction (TAIL-PCR) [36] with T-DNA border primers, as described in a previous study [37]. The PCR reactions using right border (RB) primers produced two distinct bands (RB-A and RB-B), but the left border (LB) primers produced no detectable band.…”
Section: Author Summarymentioning
confidence: 99%